Keragaan Vegetatif Dan Generatif Beberapa Varietas Tanaman Padi ( Oryza Sativa L. ) Terhadap Cekaman Kekeringan Pada Fase Pertumbuhan Yang Berbeda - Hariyono, Hariyono (Universitas Muhammadiyah Yogyakarta, 2014)
The research was conducted to study the effects of drought stress conditions on the performance of vegetative and generative of various rice varieties on the different growth stages. The research was performed at field trial of Faculty of Agriculture, Muhammadiyah University of Yogyakarta, Kasihan Bantul, from March to June 2010. The research was designed using a factorial experiment that arranged in Completely Randomized Design 4 x 5 with three replications. The first factor was the varieties of rice i.e. IR 64, Menthik, Cisadane and Dodokan. The second factor was the period of drought stress at the difference plant stage, i.e at the vegetative period, booting period, heading period, grain filling period, and without drought stress or control.The results showed that Cisadane varieties had a higher tolerance to the drought stress than to all varieties. Moreover, the plant treated on drought stress at vegetative period had lower grain number per hill than the other drought stress period.